(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
This paper analyses the determinants of the demand for defence expenditurein the NATO countries during the period 1996-2006. Thestudy has been approached through three different sets of variables, relatedto economic aspects, strategic and military factors and politicalissues. The empirical analysis has employed dynamic panel data andthe results highlight the important role played by inertia in the nations’defence budgets over time, the unequal effect of income, the effect ofrelative prices and the existence of a spill-in effect (replacement of ownexpenditure by expenditure of allied nations).